Constrangimento e sublime : o processo racional de acesso a um território transcendental na obra de Jason Martin - Loureiro, Domingos, 1977- (2017)
This article describes, from an innovative point of view, how the manifestation of the sublime is associated with constraint and, in what way, artists have ascertained and applied it in their artistic practice. It is presented in the work of Jason Martin, as the technique is used to induce a intense phenomenological process able to provide a manifestation of a sublime experience, and in that sense the linkage between the first time in a rational order, gives rise to the manifestation the second, entered the territory of the transcendental